The need to legislate the identification of ahydro project - Tarazona Ángeles, Germán (2016)
This article makes an approach to legislation relating to hydraulic power generation resources, and describes problems arising from lack of legislation to protect the identification of a hydroelectric project, propose some guidelines that could be collected in the regulations to enhance the development of energy projects with water resources.The importance of this paper is based in the Peruvian hydroelectric potential to develop the power generation activity, this power must be exploited to the maximum for greater investment in this sector and reduce the infrastructure gap that the country currently has.